The Influence Of Service Quality On Consumer Satisfaction At The Drip Coffee And Cafe Soppeng Regency - Muh. Rezky Risandi; Aulia, Aulia; Asdar, Asdar (CV. AFDIFAL MAJU BERKAH, 2024)
This study investigates the impact of service quality on customer satisfaction at The Drip Coffee & Cafe in Soppeng Regency. A quantitative research method was employed for this analysis. The study's population includes all patrons of The Drip Coffee & Cafe in Soppeng Regency, while the sample consists of 51 customers selected from this group. Data collection was carried out using questionnaires and documentation (primary data). Analysis performed using Statistical Package for the Social Science (SPSS) version 29 revealed a significant positive influence of service quality on customer satisfaction. Specifically, the data analysis showed a coefficient value of 0.206 with a significance level of 0.001, less than 0.05. This indicates a positive and direct relationship between service quality and customer satisfaction.